Lower tumorigenesis without life extension in rats receiving lifelong deep ocean minerals. (3rd April 2020) - Saovieng, Suchada; Wu, Jinfu; Jean, Wei‐Horng; Huang, Chih‐Yang; Higgins, Matthew F.; Alkhatib, Ahmad; Korivi, Mallikarjuna; Chen, Chiao‐Nan; Kuo, Chia‐Hua
Abstract: Naturally occurring tumor in animals receiving high minerals from deep oceans (DOM: hardness 600 mg/L) from 6 months of age until natural death was firstly assessed in 200 Sprague Dawley rats, randomized into four groups: Control (C), DOM (D), Fructose (F), and Fructose + DOM (FD). Fructose drink contained 11% fructose. Tumor incidence (necropsy at death) in the D group was ~40% lower than that in the C group ( P  < .05), together with lower body mass gain and greater locomotive activity during their initial 18 months ( P  < .05) but not during later life. X‐ray image analysis on abnormal solid tissue among survivors at 18 and 24 months of age confirms a similar trend, exhibiting ~50% and ~65% lower tumor incidence than the C and F groups, respectively. Reduced‐to‐oxidized glutathione ratio (GSH/GSSG) declined with age for the first three quarters of life on all groups ( P  < .05), followed by a resurgence during end‐life among survivors at 24 months. This resurgence is markedly associated with lower tumor expansion but unrelated with DOM supplementation. Our results demonstrate valuable application of minerals and trace elements from deep oceans, as a vastly available natural source, on tumor suppression during normal aging. Abstract : Tumor incidence increases with advancing aging. Lifelong supplementation of deep ocean minerals significantly suppresses age‐associated tumorigenesis. This tumor‐suppressive action is associated with preventing weight gain and increasing spontaneous physical activity during the first two‐thirds period of life.